Remote Monitoring and Control of Electrical Appliances in Home for Economic Power Management by Using GSM & Android Application - Veerasundaram, M; Duraimurugan, M; Karthickraj, S; M. Sathish, K; Srivenkatesh, R (International Journal of Engineering and Technology, 2018)
The main objective of this paper is to monitor and control all the household electrical appliances with the help of GSM and android application. The system continually monitorsÂ voltage and current and calculate the power consumed for every 24 hours and also calculates the cost of the energy consumed by the load. The proposed system is low of cost, flexible in operation and provides benefits for both ends.Â Â